Answer:
-2
Step-by-step explanation:
The average rate of change on an interval is ...
average rate of change = (amount of change)/(width of interval)
= (-3 -1)/(1 -(-1)) = -4/2 = -2
The average rate of change between (-1, 1) and (1, -3) is -2.
Answer:
(5a^2-4)*(25a^4+20a^2+16)
Step-by-step explanation:
Answer:
4.3 *10^3
Step-by-step explanation:
Answer:
52/997
Step-by-step explanation:
i just know and i checked it on khan academy
Answer
It takes two steps to solve this problem. Step 1, you must solve the binomial squared. Then combine similar terms.